(untitled) (Research, Society and Development, 2020)
The objective of this study was to verify the vocal measurements of athletes from an american football team from a municipality in the countryside of the state. With participation of eight men, aged between 18 and 39 years old (average of 24.25 years old). The collection of maximum phonation time of the vowels /a/, /i/, /u/, /s/, /z/, /e/ and number counting in normal pitch and loudness and the maximum phonation time of the [ė] was performed. Modal Sound Pressure Level and dynamic range were obtained by emission of /a:/. Acoustic evaluation of glottal and spectrographic sources. Maximum phonation times were below normality; the s/z ratio within the normality; the ratio ė/e below normality; the difference between vowels and number counting, the modal sound pressure level and the dynamic range were above normality. The acoustic vocal analysis showed impairment of the glottic source while the spectrographs were considered normal. In these American football athletes, pneumo-phono-articulatory incoordination with hyperfunctional characteristics and acoustic signal with presence of instability, aperiodicity and vocal emission failures were found, probably due to the incorrect vocal uses practiced in the sport.